IMPLEMENTASI ALAT BANTU PERTANIAN MAN-TOOLS KNM DESA TEJAMULYA UNIVERSITAS MAJALENGKA - Ardi Mardiana; Enang Rusnandi; Deffy Susanti (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
In the agricultural sector, the role of tools, the grouping of agricultural tolls and machines cannot be separated from the definition of the tools and machines can be distinguished from the general case because a machine can be driven by human power or automatically. Reflecting on the modern agricultural system that has been implemented in developed countries, such as Japan, America, and China. The pattern of agriculture in Indonesia must immediately improve. The reason is that most farmers in Indonesia have not been able to maximize the development of tools, technology and utilize modern agricultural tools to boost the productivity of the rice fields.